Comparison of catheter-over-needle and catheter-through-needle methods in ultrasound-guided continuous femoral nerve block: A prospective, randomized controlled trial. Issue 26 (2nd July 2021) - Kim, Hee Young; Ahn, Ji-Soo; Park, Seyeon; Choi, Eun-Ji; Ri, Hyun-Su; Yoon, Ji-Uk; Byeon, Gyeong-Jo
Abstract: Background: The catheter-through-needle (CTN) method involves the insertion of a catheter with an outer diameter smaller than the initial puncture hole. We investigated whether the catheter-over-needle (CON) method is more effective than the CTN method in local anesthetic leakage at the catheter insertion site and catheter dislodgement, and how it affects postoperative pain management. Methods: Seventy patients scheduled to undergo continuous femoral nerve block for pain control following total knee arthroplasty were enrolled and randomized to receive a perineural catheterization with either the CTN method (group CTN) or CON method (group CON). After ultrasound-guided catheterization, the transparent securement dressing was attached. The study compared the CON and CTN methods in terms of leakage at the catheter insertion site, catheter dislodgement, and postoperative analgesic efficacy for 48 hours postoperatively. Results: Leakage at the catheter insertion site was significantly lower in the group CON ( P  < .05), while catheter dislodgement was not significantly different between the groups. The other adverse events were not different between the groups. The procedure time was significantly shorter in group CON ( P  < .05). No significant intergroup differences were observed 48 hours postoperatively in the visual analog scales, the number of patients requiring additional analgesics, and the number of times a bolus dose was injected with an injection pump. Conclusion: The CON method was able to shorten the procedure time while reducing the incidence of leakage at the catheter insertion site than the CTN method, and showed similar effects in postoperative pain management.